Fresno County Young Lawyers Association Halloween Dance at Crossland's Barn - Watkins, Howard::::::::: (1984)
Dave Maybary holding saxophone, Fransen and Lorraine Bolen singing; Hal Bolen on drums and Bob Fishman playing guitar